Penerapan Metode Extreme Programming (XP) Dalam Membangun Aplikasi Penjualan Produk BUMDES Teluk Latak Berbasis Mobile - Bella Kurnia Amellia; Muhammad Asep Subandri (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
Village-Owned Enterprises (BUMDes) are a crucial instrument in village economic development, serving as a vehicle for managing local potential and driving the independence of village communities. However, in practice, many BUMDes still face challenges, particularly in terms of marketing management and transaction recording, which are still carried out manually. This condition also occurs in the Teluk Latak BUMDes, where the limitations of the manual system result in inefficient marketing processes, poorly documented transaction recording, and limited market reach. In response to these challenges, this study aims to design and build a mobile-based BUMDes product sales application that can support business activities in a more modern and integrated manner. The system development method used is Extreme Programming (XP), a software engineering approach oriented towards rapid iteration, close collaboration with users, and continuous testing. The stages in the XP method, such as planning, design, coding, and testing, are systematically applied to ensure the developed application meets user needs. The resulting application is equipped with product management features, online ordering, digital payments, and real-time transaction notifications. System testing was conducted using the Black Box Testing method, which showed that all application functions ran according to requirements and no errors were found during the trial. With this mobile-based sales application, BUMDes is expected to improve transaction management efficiency, expand market access through digital services, and strengthen the competitiveness of local products. Furthermore, the application's implementation has the potential to support sustainable village economic development through the use of information technology.